Six new species of Tonsilla Wang & Yin, 1992 (Araneae: Agelenidae) from southern China, with the first description of the male of T. yanlingensis (Zhang, Yin & Kim, 2000) - Zhang, Meng; Irfan, Muhammad; Wang, Lu-Yu; Zhang, Zhi-Sheng (Zootaxa, 2022)
Six new species of the spider genus Tonsilla Wang & Yin, 1992 are described from southern China: T. jinyunensis sp. nov. (♂♀) from Chongqing, T. jiugongensis sp. nov. (♂♀) from Hubei, T. subtruculenta sp. nov. (♂♀), T. rutunda sp. nov. (♂♀) and T. yueliangensis sp. nov. (♂) from Guizhou and T. subrostrum sp. nov. (♂♀) from Hunan. In addition, T. yanlingensis (Zhang, Yin & Kim, 2000) is redescribed and its male is described here for the first time. Tonsilla subyanlingensis Liu & Xu, 2020 is transferred to Draconarius Ovtchinnikov, 1999, hence the new combination Draconarius subyanlingensis (Liu & Xu, 2020) comb. nov. is established. The female of T. subyanlingensis Liu & Xu, 2020 should be treated as T. yanlingensis (Zhang, Yin & Kim, 2000). Detailed descriptions, photographs of copulatory organs and somatic features, a distribution map and comparisons with closely related species are presented.